Incorporating an ambient agent to support people with a cognitive vulnerability - Ab. Aziz, Azizi; Klein, Michel C. A. (Springer Berlin Heidelberg, 2012)
This article presents the design of an intelligent agent application aimed at supporting people with a cognitive vulnerability to prevent the onset of a depression. For this, a computational model of the cognitive processes around depression is used. The agent application uses the principles of Rational Emotive Behavioural Therapy (RBET). The effect of the application is studied using software simulation.The simulation shows that a person that responds to REBT therapy develops less cognitive vulnerability than people that are not supported.